Artonin E Induces Apoptosis via Mitochondrial Dysregulation in SKOV-3 Ovarian Cancer Cells - Mashitoh Abd Rahman; Faiqah Ramli; Hamed Karimian; Firouzeh Dehghan; Noraziah Nordin; Hapipah Mohd Ali; Syam Mohan; Najihah Mohd Hashim (Public Library of Science, 2024)
Indexed by Scopus